Photoluminescence of localized excitons in ZnCdO thin films grown by molecular beam epitaxy. (July 2016) - Wu, T.Y.; Huang, Y.S.; Hu, S.Y.; Lee, Y.C.; Tiong, K.K.; Chang, C.C.; Shen, J.L.; Chou, W.C.
Abstract: We have investigated the luminescence characteristics of Zn1− x Cd x O thin films with different Cd contents grown by molecular beam epitaxy system. The temperature-dependent photoluminescence (PL) and excitation power-dependent PL spectra were measured to clarify the luminescence mechanisms of the Zn1− x Cd x O thin films. The peak energy of the Zn1− x Cd x O thin films with increasing the Cd concentration is observed as redshift and can be fitted by the quadratic function of alloy content. The broadened full-width at half-maximum (FWHM) estimated from the 15 K PL spectra as a function of Cd content shows a larger deviation between the experimental values and theoretical curve, which indicates that experimental FWHM values are affected not only by alloy compositional disorder but also by localized excitons occupying states in the tail of the density of states. The Urbach energy determined from an analysis of the lineshape of the low-energy side of the PL spectrum and the degree of localization effect estimated from the temperature-induced S-shaped PL peak position described an increasing mean exciton-localization effects in ZnCdO films with increasing the Cd content. In addition, the PL intensity and peak position as a function of excitation power are carried out to clarify the types of radiative recombination and the effects of localized exciton in the ZnCdO films with different Cd contents. Highlights: Temperature-dependent PL spectra of Zn1− x Cd x O films have been investigated. The relationships between experimental and theoretical PL linewidth are discussed. Obvious temperature-induced S-shaped PL is related to large excitonic localization. The empirical Urbach energy has been determined from the asymmetric PL lineshape. The types of radiative processes are clarified by excitation power-dependent PL.